Efectos de la putrescina en diferentes ciclos de selección masal divergente del maíz harinoso mosquera i sin. 2 afectados por las heladas (1990)
During 1989, at the Tibaitata Research Center, an experiment plot was carried out. On cycles 6, 9, 12 and 15 of prolific and non prolific corn sub-populations which treated with 0, 1000, 2000 and 4000 Mm of putrescine. Six hours before aplication, the corn plants suffered chilling effects (-1.50 C/4 hr). As consecuence of chilling, the growth in height was suspended, the ear shoots and yield grain decreased. However putrescine application reverted the damage caused hy chilling and significative differences were observed in height and yield grain. Cicle 6 in prolific sub population was noticeable, in which 1000, 2000, and 4000 Mm of putrescine yielded 6.75, 5.24 and 5.63 Ton/ha. The Harinoso Mosquera I. Sin. 2 or cycle cero, showed a higber sensibility to chilling and the answer to putrescine application was almost negligeable.